CgGCS, Encoding a Glucosylceramide Synthase, Is Required for Growth, Conidiation and Pathogenicity in Colletotrichum gloeosporioides - Huang, Yimei (Front Microbiol, 2019)
Fungal glucosylceramide plays important role in cell division, hyphal formation and growth, spore germination and the modulation of virulence and has recently been considered as target for small molecule inhibitors. In this study, we characterized CgGCS, a protein encoding a glucosylceramide synthase (GCS) in Colletotrichum gloeosporioides. Disruption of CgGCS resulted in a severe reduction of mycelial growth and defects in conidiogenesis. Sphingolipid profile analysis revealed large decreases in glucosylceramide production in the mutant strains. Pathogenicity assays indicated that the ability of the ΔCgGCS mutants to invade both tomato and mango hosts was almost lost. In addition, the expression levels of many genes, especially those related to metabolism, were shown to be affected by the mutation of CgGCS via transcriptome analysis. Overall, our results demonstrate that C. gloeosporioides glucosylceramide is an important regulatory factor in fungal growth, conidiation, and pathogenesis in hosts.